2020
DOI: 10.3114/fuse.2020.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Japanese species of Alternaria and their species boundaries based on host range

Abstract: To clarify the diversity of plant-parasitic Alternaria species in Japan, diseased samples were collected, and fungal isolates established in culture. We examined 85 isolates representing 23 species distributed in 14 known sections based on conidial morphology and DNA phylogeny. Three species were found to be new, A. cylindrica, A. paragomphrenae and A. triangularis. Furthermore, a lectotype was designated for A. gomphrenae, and epitypes for A. cinerariae, A. gomphrenae, A. iridicola, and A. japonica. Specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 93 publications
(172 reference statements)
1
22
1
Order By: Relevance
“…Although calibrachoa is popular as a potted plant crop in many regions, little is known about the diseases these plants may develop, maybe because it is a relatively new crop. Among the pathogens previously reported on calibrachoa, only A. porri causes leaf spots (Nishikawa and Nakashima, 2020). The symptoms were not described but Alternaria leaf spots on many plants are clearly distinct from the ones we found associated with N. oryzae in calibrachoa.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Although calibrachoa is popular as a potted plant crop in many regions, little is known about the diseases these plants may develop, maybe because it is a relatively new crop. Among the pathogens previously reported on calibrachoa, only A. porri causes leaf spots (Nishikawa and Nakashima, 2020). The symptoms were not described but Alternaria leaf spots on many plants are clearly distinct from the ones we found associated with N. oryzae in calibrachoa.…”
Section: Resultscontrasting
confidence: 60%
“…To date, Calibrachoa mottle virus (CbMV) (Liu et al, 2003), Tobacco mild green mosaic virus (TMGMV) (Sabanadzovic et al, 2009), Podosphaera xanthii (Brielmaier-Liebetanz et al, 2015), Phytophthora nicotianae (Lin et al, 2018), Potato virus Y (PVY) (Tombion et al, 2019), Alternaria porri (Nishikawa and Nakashima, 2020), and Sclerotinia sclerotiorum (Borrelli et al, 2020), have been reported to infect calibrachoa plants in different countries. The development of new cultivars includes disease surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The year 1933 was a decisive one, because the researchers came to the conclusion that the genus Macrosporium should be called "nomen ambiguum" (Singh et al, 2016;Lawrence et al, 2016Lawrence et al, , 2013. This decision was based on the fact that problems occurred because of the numerous taxons that were superficially investigated, and more than 400 fake species were described (Nishikawa and Nakishima, 2020 The fifth stage was between 2003-2015, when the reclassification of the genus Alternaria and other related species, through DNA analysis was elaborated. The first approach of this was performed on the genus Stemphylium and Ulocladium.…”
Section: The History Of the Taxonomic Classification And The Current mentioning
confidence: 99%
“…Caliciopsis arceuthobii infects the flowers of several species of dwarf mistletoe in the genus Arceuthobium (Ramsfield et al 2009), Caliciopsis rhoina is associated with bark and trunk cankers on Toona sinensis (Rikkinen 2000), while Caliciopsis brevipes was reported on needles and bark of Araucaria araucana and C. cochlearia on needles and twigs of A. araucana, Fitzroya cupressoides, Austrocedrus chilensis, Pilgerodendron uviferum and Podocarpus nubigenus (Butin 1970). More recently, Caliciopsis pleomorpha [now recombined in Hypsotheca as H. pleomorpha (Crous et al 2019)] has been reported as the causal agent of a canker disease on various Eucalyptus species in Australia (Pascoe et al 2018).…”
Section: Introductionmentioning
confidence: 99%